Age-Related Differences in Hospitalization Rates, Clinical Presentation, and Outcomes Among Older Adults Hospitalized With Influenza—U.S. Influenza Hospitalization Surveillance Network (FluSurv-NET). (1st June 2019) - Czaja, Christopher A; Miller, Lisa; Alden, Nisha; Wald, Heidi L; Cummings, Charisse Nitura; Rolfes, Melissa A; Anderson, Evan J; Bennett, Nancy M; Billing, Laurie M; Chai, Shua J; Eckel, Seth; Mansmann, Robert; et al.
Abstract: Background: Rates of influenza hospitalizations differ by age, but few data are available regarding differences in laboratory-confirmed rates among adults aged ≥65 years. Methods: We evaluated age-related differences in influenza-associated hospitalization rates, clinical presentation, and outcomes among 19 760 older adults with laboratory-confirmed influenza at 14 FluSurv-NET sites during the 2011–2012 through 2014–2015 influenza seasons using 10-year age groups. Results: There were large stepwise increases in the population rates of influenza hospitalization with each 10-year increase in age. Rates ranged from 101–417, 209–1264, and 562–2651 per 100 000 persons over 4 influenza seasons in patients aged 65–74 years, 75–84 years, and ≥85 years, respectively. Hospitalization rates among adults aged 75–84 years and ≥85 years were 1.4–3.0 and 2.2–6.4 times greater, respectively, than rates for adults aged 65–74 years. Among patients hospitalized with laboratory-confirmed influenza, there were age-related differences in demographics, medical histories, and symptoms and signs at presentation. Compared to hospitalized patients aged 65–74 years, patients aged ≥85 years had higher odds of pneumonia (aOR, 1.2; 95% CI, 1.0–1.3; P = .01) and in-hospital death or transfer to hospice (aOR, 2.1; 95% CI, 1.7–2.6; P < .01). Conclusions: Age-related differences in the incidence and severity of influenza hospitalizations among adults aged ≥65 years can inform prevention and treatment efforts, and data should be analyzed and reported using additional age strata. Abstract : Rates of hospitalization and risk of death from seasonal influenza increase with age among persons aged ≥65 years; influenza surveillance data from older adults should be analyzed and reported using additional age strata.